Production of bio-hydrogen from dairy wastewater using pretreated landfill leachate sludge as an inoculum - Wong, Yee Meng; Show, Pau Loke; Wu, Ta Yeong; Leong, Hui Yi; Ibrahim, Shaliza; Juan, Joon Ching (Elsevier, 2019)
Bio-hydrogen production from wastewater using sludge as inoculum is a sustainable approach for energy production. This study investigated the influence of initial pH and temperature on bio-hydrogen production from dairy wastewater using pretreated landfill leachate sludge (LLS) as an inoculum. The maximum yield of 113.2 ± 2.9 mmol H 2 /g chemical oxygen demand (COD) (12.8 ± 0.3 mmol H 2 /g carbohydrates) was obtained at initial pH 6 and 37 °C. The main products of volatile fatty acids were acetate and butyrate with the ratio of acetate:butyrate was 0.4. At optimum condition, Gibb's free energy was estimated at −40 kJ/mol, whereas the activation enthalpy and entropy were 65 kJ/mol and 0.128 kJ/mol/l, respectively. These thermodynamic quantities suggest that bio-hydrogen production from dairy wastewater using pretreated LLS as inoculum was effective and efficient. In addition, genomic and bioinformatics analyses were performed in this study. © 2018 The Society for Biotechnology, Japan